The Vitamin D Receptor Gene Polymorphisms in Asthmatic Children: A Case-Control Study - Kilic, Mehmet; Ecin, Sema; Taskin, Erdal; Sen, Askin; Kara, Murat (Mary Ann Liebert, Inc, 2019)
Background: The association between vitamin D receptor (VDR) polymorphisms and the risk of asthma remains unclear. This study aimed to investigate the effect of VDR gene polymorphisms and VDR mRNA expression levels on respiratory function, nitric oxide levels in expiratory air, and serum vitamin D levels in children with asthma. Materials and Methods: The study included 80 healthy children (control group) and 100 asthmatic children (asthma group) between the age of 5 and 18 years. The VDR genotypes (ApaI, TaqI, and FokI) and VDR mRNA levels were determined in all groups. Results: There was no statistically significant difference in vitamin D levels between the asthma group and the control group (P > 0.05). A significant association was found between both genotype (CC) of the TaqI polymorphism [odds ratio (OR) = 0.2, 95% confidence interval (CI) (0.07-0.5), P = 0.003] and genotype (CA) of ApaI polymorphisms [OR = 0.2, 95% CI (0.07-0.8), P = 0.02], and asthma risk. In addition, when single-nucleotide polymorphism allelic frequencies between asthma and control groups were compared there is no significant association (P > 0.05). When compared to control group, VDR mRNA expression in asthma group decreased in genotypes CC and CA of ApaI and in genotypes TT and TC of TaqI (P < 0.05). Conclusion: The results provide supporting evidence for an association between TaqI and ApaI polymorphisms and asthma susceptibility.
Keywords: asthma; vitamin D; exhaled nitric oxide; VDR gene polymorphism; VDR mRNA expression